Clinical and Ultrasound‐Based Composite Disease Activity Indices in Rheumatoid Arthritis: Results From a Multicenter, Randomized Study. Issue 6 (30th May 2013) - Mandl, P.; Balint, P. V.; Brault, Y.; Backhaus, M.; D'Agostino, M. A.; Grassi, W.; van der, D.; de, E.; Wakefield, R. J.; Logeart, I.; Dougados, M.
<x xml:space="preserve">Abstract</x> Objective To evaluate the metrologic properties of composite disease activity indices in rheumatoid arthritis (RA), utilizing information derived from clinical, gray‐scale (GS), and power Doppler (PD) ultrasound examinations, and to assess the classification of patients according to disease activity using such indices. Methods This ancillary study utilized data from a multicenter, prospective, randomized, parallel‐group study conducted in subjects with moderate RA randomized to receive etanercept and methotrexate (ETN + MTX) or usual care (various disease‐modifying antirheumatic drugs [DMARDs]). In multimodal indices, the 28 swollen joint count was either supplemented or replaced by clinically nonswollen joints in which the presence of synovitis was detected either by GS and/or PD and was calculated according to the Disease Activity Score in 28 joints (DAS28) or the Simplified Disease Activity Index (SDAI). Reliability, external validity, and discriminative capacity were calculated at baseline/screening by intraclass correlation coefficient, Pearson's correlation, and standardized response mean, respectively. Results Data from 62 patients (mean ± SD age 53.8 ± 13.2 years, mean ± SD disease duration 8.8 ± 7.7 years, mean ± SD disease activity 4.6 ± 0.5 [DAS28] and 20.9 ± 5.9 [SDAI]) were analyzed, with 32 receiving ETN + MTX and 30 receiving DMARDs. The metrologic properties were at least as good for GS‐ and/or PD‐based indices as for their clinical counterparts. Using GS‐ and PD‐supplemented indices, an additional 67.8% and 32.3% of patients (DAS28‐derived and SDAI‐derived indices, respectively) could be classified as having high disease activity at the screening visit. Conclusion Multimodal indices incorporating ultrasound and clinical data had similar metrologic properties to their clinical counterparts; certain indices allowed for a significantly larger number of patients to be classified to either high or moderate disease activity at the screening visit.